GEOTECHNIC ANALYSIS OF SLOPE STABILITY FOR OPEN COAL MINING SYSTEM DESIGN IN EAST KALIMANTAN - Yana Rahmat Riyanto (Jurnal Scientia, 2023)
According to observations made at the mine site, there were several small landslides in almost every mine pit, but overall the slopes of the mine walls were in good condition. Slope stability studies were carried out on mine slopes and the results of the process of piling up overburden material in open pit mining systems, both of which have varying treatment and holding strength. In order to assess the effectiveness of the planned slope design in pit 7, a slope stability analysis must be carried out. Samples that have been subjected to laboratory testing, both for physical and mechanical properties, must be consistent with and under the same conditions as when the sample was first taken at the research location. The results of this study stated that on the highwall slope the slope design at a height of -101.6 which is planned to be unsafe with a safety factor value of 1.16 is what causes the highwall slope on cross section D. The unsafe FK value for the highwall slope 2 part of the F slope is 1.19. The final slope design on the slope of section G which is expected to be affected by the load of material disposal has an FK value of 1.23 which indicates it is not safe. As for the sidewall slopes, the final design of the sidewall slope sections is influenced by modeling findings. The critical FK value of 1.25 occurs at an altitude of -61 masl which is influenced by the material disposal load. The final design slope is in an unsafe condition with a safety factor value of 1.21 at an elevation of 77 masl, according to the modeling results for the J-section model